BAIAP2L2 is required for the maintenance of mechanotransducing stereocilia of cochlear hair cells. Issue 1 (4th August 2021) - Yan, Keji; Zong, Wen; Du, Haibo; Zhai, Xiaoyan; Ren, Rui; Liu, Shuang; Xiong, Wei; Wang, Yanfei; Xu, Zhigang
Abstract: Stereocilia are actin‐based cell protrusions of inner ear hair cells that play an essential role in mechano‐electrical transduction (MET). Stereocilia are organized into several rows of increasing heights with the MET protein complex localized at the tips of shorter row stereocilia. At the tips of shorter row mechanotransducing stereocilia also resides a so‐called "row 2 protein complex" whose dysfunction causes degeneration of the mechanotransducing stereocilia. In the present work, we show that BAIAP2L2 is localized at the tips of shorter row stereocilia in neonatal and adult mouse cochlear hair cells. Baiap2l2 inactivation causes degeneration of the mechanotransducing stereocilia, which eventually leads to profound hearing loss in mice of either sex. Consistently, electrophysiology and FM 1‐43FX dye uptake results confirm that MET currents are compromised in Baiap2l2 knockout mice. Moreover, BAIAP2L2 binds to known row 2 complex components EPS8L2, TWF2, and CAPZB2, and the stereociliary tip localization of CAPZB2 is dependent on functional BAIAP2L2. Interestingly, BAIAP2L2 also binds to CIB2, a known MET complex component, and the stereociliary tip localization of BAIAP2L2 is abolished in Cib2 knockout mice. In conclusion, our present data suggest that BAIAP2L2 is a row 2 complex component, and is required for the maintenance of mechanotransducing stereocilia. Meanwhile, specific MET components such as CIB2 might play a direct role in stereocilia maintenance through binding to BAIAP2L2. Abstract : BAIAP2L2 is a component of the row 2 protein complex and is required for the maintenance of mechanotransducing stereocilia of cochlear hair cells. Moreover, MET component CIB2 might play a direct role in stereocilia maintenance through binding to BAIAP2L2.